Morphological alterations of the choroid plexus epithelium in Alzheimer's disease: Molecular and cell biology/APP/abeta/amyloid. (7th December 2020) - Van Cauwenberghe, Caroline; Vandendriessche, Charysse; Kremer, Anneke; De Rycke, Riet; Borghgraef, Peter; Van Imschoot, Griet; Van Wonterghem, Elien; Lippens, Saskia; Vandenbroucke, Roosmarijn E
Abstract: Background: The choroid plexus (CP), is a complex structure localized in the ventricles of the brain, which mainly consist of tightly connected choroid plexus epithelial (CPE) cells surrounding fenestrated capillaries. These CPE cells form the blood‐cerebrospinal fluid barrier and play a vital role in the maintenance of brain homeostasis. During Alzheimer's disease (AD) several CPE related processes are severely affected (Brkic, 2015) and evidence indicates that CP‐derived extracellular vesicles play an important role in AD pathogenesis. In this study morphological alterations of the CPE cells were characterized in two distinct AD mice models (APP/PS1 tg/wt and APP NLGF/NLGF ). Additionally, we investigated the subcellular localization and performed quantification of multivesicular bodies (MVBs) and intraluminal vesicles (ILVs) using transmission electron microscopy (TEM) and 3D‐scanning electron microscopy (3D‐SEM). Method: CP tissue was isolated from APP wt/wt, APP/PS1 tg/wt, APP NLGF/NLGF mice at different timepoints (age 10w, 20w, 30w and 40w). Isolated CP was processed for TEM and 3D‐SEM imaging as previously described in (Balusu, 2016; Kremer, 2015). Visualization of the samples was performed using a TEM (JEOL) and FIB‐SEM (Zeiss) and manual segmentation of 3D‐SEM images was done using Microscopy Image Browser (Belevich, 2016). Result: In both APP/PS1 tg/wt and APP NLGF/NLGF mice morphological alterations of the CP are visible at the age of 20 weeks, the ultrastructure is damaged. The CPE cells lose their typical cuboidal shape, are more point‐shaped, the cytoplasm becomes more translucent, the nuclei are irregularly shaped and the mitochondria are more condensed. These changes become increasingly prominent as the mice age. In APP wt/wt mice, the same morphological alterations of the CP become visible at later age. Early during disease progression (10 w), we observed higher levels of ILVs in the CP of APP/PS1 tg/wt compared to age‐matched APP wt/wt mice, while levels normalized at later stages. In APP NLGF/NLGF mice higher MVB and ILV levels are observed early during disease progression. Conclusion: Ultrastructural changes of the CP epithelium are present in different AD mice models. Furthermore, we observed differences in levels of ILVs in the CP early during disease progression. Further research might give insights into the role of the CP and ILVs in AD pathogenesis.